Octa-substituted bromonaphthyl metallophthalocyanines as potent photosensitizers for singlet oxygen generation in SPDT - Kilicarslan, Fatma Aytan; Gokcil, Gookce; Atmaca, Goknur Yasa; Erdogmus, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Singlet oxygen in biological systems is primarily produced via photosensitization, where an excited sensitizer transfers energy to molecular oxygen. In photodynamic therapy (PDT), this reactive oxygen species is employed to induce cancer cell death. Sono-photodynamic therapy (SPDT), integrating ultrasound and light activation, offers enhanced singlet oxygen quantum yields. In this study, peripheral octa-4-[(6-bromonaphthalen-2-yl)oxy] substituted metallophthalocyanines were synthesized and characterized in terms of their spectral, aggregation, and sono-photochemical properties. Their efficacy as photosensitizers was evaluated under both photochemical and sono-photochemical conditions. The singlet oxygen quantum yields (Phi Delta) obtained in photochemical studies were 0.68 for ZnPc, 0.76 for InPc, and 0.54 for MgPc. In sono-photochemical studies, these values increased to 0.87, 0.94, and 0.68, respectively, indicating a clear enhancement of singlet oxygen generation through the synergistic effect of ultrasound and light. Overall, the results demonstrate that the designed metallophthalocyanines possess favorable photochemical and sono-photochemical characteristics, suggesting their strong potential as dual-function photosensitizer candidates for both PDT and SPDT applications.
Keywords: Phthalocyanine; Sono-photodynamic therapy; Combination therapy; Singlet oxygen; PHTHALOCYANINES; Chemistry; Crystallography